2007
DOI: 10.1016/j.ica.2006.10.041
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, and characterization of a sterically encumbered dioxo molybdenum (VI) core

Abstract: Dioxo-Mo VI complexes of general formula Tp*MoO 2 (p-SC 6 H 4 Dn) (6a-6c) (where Tp* = hydrotris (3,5-dimethyl-pyrazol-1-yl)borate and Dn= dendritic unit) have been synthesized and characterized by spectroscopy and mass spectrometry. 1 H NMR spectra of the metal complexes indicate that the C s local symmetry about the metal core does not change by the incorporation of dendritic functionality at the thiophenolato ring. Electrochemical data show ∼20 mV change in the redox potential in the complexes with dendriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…This topological feature may be a protective mechanism from dimerization of the molybdenum center, a pervasive reaction in synthetic oxo-transferring molybdenum complexes. 139 Model studies have shown that not only does this topological feature protect the Mo-centers from dimerization, 140,141 but also changes the electronic structure of the center via modulation of metal–sulfur covalency. This alteration in covalency along with a change in the dielectric properties alters the reduction potential of the molybdenum center, thus providing the driving force of the reaction.…”
Section: Nitrate Reductionmentioning
confidence: 99%
“…This topological feature may be a protective mechanism from dimerization of the molybdenum center, a pervasive reaction in synthetic oxo-transferring molybdenum complexes. 139 Model studies have shown that not only does this topological feature protect the Mo-centers from dimerization, 140,141 but also changes the electronic structure of the center via modulation of metal–sulfur covalency. This alteration in covalency along with a change in the dielectric properties alters the reduction potential of the molybdenum center, thus providing the driving force of the reaction.…”
Section: Nitrate Reductionmentioning
confidence: 99%
“…Dendrimeric species of the type [Tp*MoO 2 ( p ‐SC 6 H 4 Dn)] (Dn = dendritic unit) have also been prepared and are observed to react with phosphanes in the gas phase …”
Section: Oat and Cept Reactionsmentioning
confidence: 99%
“…Cyclic voltammograms for all dioxo complexes are shown in Figure 7, which show oneelectron quasi-reversible redox couple, assigned to Mo V /Mo VI process. 30,34 No other reductive response was observed within the solvent window. Consistent with the diffusion controlled process the peak currents follow linear relation with the square root of the scan rate while the half-wave potentials remain independent.…”
Section: Electrochemistrymentioning
confidence: 96%
“…2-Mercaptobenzoic acid was oxidized to 1 using I 2 in ethanol. 30 Disulfides 3 and 4 were synthesized by modifying a literature procedure, 31 which included first reacting 1 with oxalyl chloride to prepare the acid chloride, 2, followed by its reaction with MeNH 2 or Me 2 NH. Compound 2 was found to be sensitive to moisture and readily hydrolyzed to 1 upon contact with moisture.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%